2002
DOI: 10.1161/01.cir.0000013424.28206.8f
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein Restores Endothelial Function in Hypercholesterolemic Men

Abstract: Background-Hypercholesterolemia is a risk factor for atherosclerosis-causing endothelial dysfunction, an early event in the disease process. In contrast, high-density lipoprotein (HDL) cholesterol inversely correlates with morbidity and mortality representing a protective effect. Therefore, we investigated the effects of reconstituted HDL on endothelial function in hypercholesterolemic men. Methods and Results-Endothelium-dependent and -independent vasodilation to intraarterial acetylcholine and sodium nitropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
233
1
13

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 422 publications
(267 citation statements)
references
References 19 publications
(10 reference statements)
13
233
1
13
Order By: Relevance
“…The ApoAI then moves to the Golgi and binds eNOS, a process that actively recruits the necessary initiating enzymes, such as AMPK, which phosphorylates and activates the enzyme. A similar in vivo mechanism (of eNOS activation by ApoAI) is supported by human clinical studies in which it was reported that acute infusions of ApoAI phospholipid discs (reconstituted HDL) can completely normalize the decreased vasomoter response in vessels of the forearm of hypocholesterolemic men (35,36). These outcomes were a result of direct restoration of the NO pathway.…”
Section: Protein Association Between Apoai and Enosmentioning
confidence: 66%
“…The ApoAI then moves to the Golgi and binds eNOS, a process that actively recruits the necessary initiating enzymes, such as AMPK, which phosphorylates and activates the enzyme. A similar in vivo mechanism (of eNOS activation by ApoAI) is supported by human clinical studies in which it was reported that acute infusions of ApoAI phospholipid discs (reconstituted HDL) can completely normalize the decreased vasomoter response in vessels of the forearm of hypocholesterolemic men (35,36). These outcomes were a result of direct restoration of the NO pathway.…”
Section: Protein Association Between Apoai and Enosmentioning
confidence: 66%
“…15 There are emerging data suggesting that high-density lipoprotein may independently and favorably effect endothelial function. [59][60][61] The effects of hypertriglyceridemia, however, are less clear.…”
Section: Dyslipidemiamentioning
confidence: 99%
“…One of them is their beneficial effect on endotheliumdependent vasorelaxation. The intravenous administration of reconstituted HDL either to hypercholesterolaemic men or to heterozygotes deficient in ATP-binding cassette A1, both of whom had initially impaired endothelium-dependent vasorelaxation, restored normal vasorelaxation [3,4]. More particularly, ex vivo experiments on isolated strips of rabbit thoracic aorta showed that HDL are able to counteract the inhibitory effect of oxidised LDL (ox-LDL) on endothelium-dependent vasorelaxation [5].…”
Section: Introductionmentioning
confidence: 99%